2014
DOI: 10.1007/s12199-014-0408-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s recognition level of medical terms as estimated by pharmacists

Abstract: Objectives The role of pharmacists in the healthcare settings is expanding and pharmacists are expected to counsel patients and/or caregivers regarding the appropriate use of a drug. However, we believe that communication between healthcare providers and patients may be limited by overestimation of patients' recognition level of medical terms by providers. The purpose of this study was to clarify patients' recognition level of medical terms, mainly related to drugs, as estimated by pharmacists to contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, an experts’ perception of the risk of exposure to medical X-rays and natural sources of radiation is significantly higher than that of the general population, while experts have lower risk perception of the radiation hazard posed by nuclear waste or accident at a nuclear installation, as compared to that of general population [ 13 ]. In addition, we have earlier demonstrated the perception gaps related to pharmaceutical terms and related issues between the lay population and medical doctors [ 14 ], pharmacists [ 15 ], and nurses [ 16 ]. To conduct risk communications in the devastated area smoothly and effectively, interventions for risk communication in areas affected by disasters should be preceded by efficacy evaluation of the methodology used.…”
Section: Introductionmentioning
confidence: 99%
“…However, an experts’ perception of the risk of exposure to medical X-rays and natural sources of radiation is significantly higher than that of the general population, while experts have lower risk perception of the radiation hazard posed by nuclear waste or accident at a nuclear installation, as compared to that of general population [ 13 ]. In addition, we have earlier demonstrated the perception gaps related to pharmaceutical terms and related issues between the lay population and medical doctors [ 14 ], pharmacists [ 15 ], and nurses [ 16 ]. To conduct risk communications in the devastated area smoothly and effectively, interventions for risk communication in areas affected by disasters should be preceded by efficacy evaluation of the methodology used.…”
Section: Introductionmentioning
confidence: 99%
“…The gaps between the basic recognition of the medical terms by laypeople and that estimated by medical doctors suggest that the possibility that patients cannot recognize much more difficult terms should be considered [24]. In addition, compared with medical doctors, pharmacists tend to overestimate patients' recognition level of medical terms [25]. Furthermore, the level of medical term recognition by patients was much higher when estimated by nurses than when estimated by medical doctors.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, we conducted a study in Japan, and it demonstrated that there was a large gap in the perception of medical terms between citizens and healthcare workers [24][25][26]. The gaps between the basic recognition of the medical terms by laypeople and that estimated by medical doctors suggest that the possibility that patients cannot recognize much more difficult terms should be considered [24].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare workers played important roles in risk communication as lecturers and/or counselors. Our research demonstrated gaps in perception of pharmaceutical terms and related issues between laypeople and medical doctors (Yoshida et al, 2013), pharmacists (Yoshida and Yoshida, 2014), and nurses (Yoshida and Yoshida, 2015). Communication between healthcare providers and patients had been limited by overestimation by providers of patients' recognition level of medical terms.…”
Section: Introductionmentioning
confidence: 84%